Static Scheduling of Periodic Hardware Tasks with Precedence and Deadline Constraints on Reconfigurable Hardware Devices. (12th May 2011) - Belaid, Ikbel; Muller, Fabrice; Benjemaa, Maher
Abstract : Task graph scheduling for reconfigurable hardware devices can be defined as finding a schedule for a set of periodic tasks with precedence, dependence, and deadline constraints as well as their optimal allocations on the available heterogeneous hardware resources. This paper proposes a new methodology comprising three main stages. Using these three main stages, dynamic partial reconfiguration and mixed integer programming, pipelined scheduling and efficient placement are achieved and enable parallel computing of the task graph on the reconfigurable devices by optimizing placement/scheduling quality. Experiments on an application of heterogeneous hardware tasks demonstrate an improvement of resource utilization of 12.45% of the available reconfigurable resources corresponding to a resource gain of 17.3% compared to a static design. The configuration overhead is reduced to 2% of the total running time. Due to pipelined scheduling, the task graph spanning is minimized by 4% compared to sequential execution of the graph.